Correlation Study on Personal Factors of General and Specialist Dentists Regarding Emergency Management of Traumatic Dental Injuries - Adrisya Lubis, Putri Anggie; Girsang, Ermi; Sihotang, Widya Yanti (Poltekkes Kemenkes Tanjung Karang, 2024)
Traumatic dental injuries are increasingly recognized as a significant dental health issue, particularly among children and adolescents. These injuries commonly result from falls, motorbike accidents, sports injuries, or violence. Both general dentists and specialists are responsible for providing emergency care for these injuries, making it essential for them to have sufficient knowledge and experience in managing such cases. This study aims to assess the personal factors influencing the emergency management of traumatic dental injuries among general dentists and specialists in Medan City. A quantitative, cross-sectional design was used, involving a total sample of 300 general and specialist dentists. Data analysis included univariate, bivariate, and multivariate methods. The results showed a significant correlation between knowledge, perception, experience, and work length in managing traumatic dental injuries (p<0.00). However, no correlation was found between age and gender with the ability to manage these injuries (p>0.00). Among the variables, knowledge was identified as the most influential factor. The study concludes that while knowledge, perception, experience, and work duration play a critical role in emergency management, age and gender do not. It is recommended that dentists in Medan continuously enhance their knowledge in this area to ensure effective treatment, reduce patient anxiety, and improve patient satisfaction.